PENGARUH NILAI PELANGGAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH KREDIT PADA PT. BPR MUTIARA NAGARI TANJUNG AMPALU - Zusmawati Zusmawati; Anggun Tri Rahmi (LP2M Universitas Bina Bangsa, 2022)
The purpose of this study was to determine and analyze the effect of customer value and service quality on customer credit satisfaction at PT. BPR Mutiara Nagari Tanjung Ampalu. The population in this study were all credit customer of PT. BPR Mutiara Nagari Tanjung Ampalu. Determining the sample using the formula Slovin, the number of respondents as a sample in this study were 86 credit customers. The data analysis technique used to test the hypothesis is the statistical t test. The results showed that customer value, empathy, and physical evidence has an effect on customer credit satisfaction at PT. BPR Mutiara Nagari Tanjung Ampalu. This is because customer value, reliability, responsiveness, assurance, empathy, and physical evidence, has a significant value is smaller than alpha 0.05